1992
DOI: 10.1007/bf02257619
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial complex I and II activities of lymphocytes and platelets in Parkinson's disease

Abstract: Mitochondrial Complex I deficiencies have been described not only in the brain but also in the skeletal muscle and platelets in Parkinson's disease (PD). We report activities of Complex I, II, III, and IV in lymphocytes and platelets in 20 patients with PD and age-matched controls. A small but a significant decrease in the platelet Complex I activity was found in PD (9.14 +/- 1.86 units/mg protein) compared with that in the control (12.37 +/- 2.66 units/mg protein) (P = 0.0002). The lymphocyte Complex I activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(121 citation statements)
references
References 27 publications
6
114
0
1
Order By: Relevance
“…Our data confirm prior studies showing complex I activity is reduced in PD subject platelets (Schapira and Marsden, 1994;Barroso et al, 1993;Parker et al, 1989;Yoshino et al, 1992;Benecke et al, 1993;Haas et al, 1995;Blandini et al, 1998). Our data further confirm and extend prior studies demonstrating mitochondrial transfer from PD subject platelets to rho0 cells produces cybrid cell lines in which complex I V max activities are reduced relative to cybrid cell lines containing mitochondria from control subjects (Swerdlow et al, 1996;Cassarino et al, 1997).…”
Section: Discussionsupporting
confidence: 91%
“…Our data confirm prior studies showing complex I activity is reduced in PD subject platelets (Schapira and Marsden, 1994;Barroso et al, 1993;Parker et al, 1989;Yoshino et al, 1992;Benecke et al, 1993;Haas et al, 1995;Blandini et al, 1998). Our data further confirm and extend prior studies demonstrating mitochondrial transfer from PD subject platelets to rho0 cells produces cybrid cell lines in which complex I V max activities are reduced relative to cybrid cell lines containing mitochondria from control subjects (Swerdlow et al, 1996;Cassarino et al, 1997).…”
Section: Discussionsupporting
confidence: 91%
“…The presence of mitochondrial defects in mice carrying PINK1 germline deletions, which genetically recapitulate pathogenic mutations in PINK1-linked PD patients, provides further support for (29,30), and in fibroblasts derived from patients bearing PINK1 pathogenic mutations (31). However, the presence of complex II and complex III/IV defects are relatively novel in a PD mouse model, although they have been previously reported for mitochondria isolated from PD patients (23,32,33). It is also worth noting that these functional defects are relatively subtle and fail to create a major energy crisis as measured by ATP levels.…”
Section: Discussionmentioning
confidence: 72%
“…but the explanation for this phenomenon was unknown (9,42,65,94,162). It was proposed that environmental or endogenously generated toxins could account for this, and several candidate toxins were considered (28,44,47,73,77,86,89,104).…”
Section: Swerdlowmentioning
confidence: 99%
“…Two decades later, the controversy over the anatomic distribution of the PD complex I defect seems to have been settled (128,131). It has repeatedly been demonstrated in PD subject platelets and muscle, and has also been demonstrated in fibroblasts and lymphocytes (7,9,12,13,18,34,42,65,85,87,94,119,162). More recently, it was shown that the original controversy likely arose entirely as a consequence of methodological issues (128) (Fig.…”
mentioning
confidence: 99%